2021
DOI: 10.1063/5.0045443
|View full text |Cite
|
Sign up to set email alerts
|

Detailed crystallographic analysis of the ice V to ice XIII hydrogen-ordering phase transition

Abstract: Ice V is a structurally highly complex material with 28 water molecules in its monoclinic unit cell. It is classified as a hydrogen-disordered phase of ice. Yet, some of its hydrogen-bonded water molecules display significant orientational order. Upon cooling pure ice V, additional orientational ordering cannot be achieved on the experimental time scale. Doping with hydrochloric acid has been shown to be most effective in enabling the phase transition of ice V to its hydrogen-ordered counterpart ice XIII. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…However, it has also been suggested that ice XIX is a new hydrogen-ordered phase of ice VI. 3,4 Calorimetric measurements of high-pressure HCldoped ice V/XIII has shown the emergence of a transient ordering regime 29 similar to what is observed for ice XIX/VI. Further experiments aiming at increasing the pressure on the ice V/XIII system could produce a deep glassy state of ice V, and yet another crystallographically unique phase of ice.…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…However, it has also been suggested that ice XIX is a new hydrogen-ordered phase of ice VI. 3,4 Calorimetric measurements of high-pressure HCldoped ice V/XIII has shown the emergence of a transient ordering regime 29 similar to what is observed for ice XIX/VI. Further experiments aiming at increasing the pressure on the ice V/XIII system could produce a deep glassy state of ice V, and yet another crystallographically unique phase of ice.…”
Section: Introductionmentioning
confidence: 55%
“…In previous work, LiOH-doped ice V was analysed and shown to successfully aid in the formation of ice XIII. 23,29 A 0.81 GPa, 0.0 1M LiOH-doped ice IV sample was therefore made and analysed as shown in thermogram 5 in Figure 3(a). But, similar to LiOH-doped ice VI, this dopant does not aid in hydrogen-ordering as this thermogram looks similar to the pure H2O ice IV thermogram.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we investigate the calorimetric behavior of the ice V–XIII pair as a model case to elucidate the hydrogen ordering process in ice. Here, ice V–XIII is selected for its three properties: (i) a completely ordered configuration can be defined for ice XIII, ,, (ii) the hydrogen order–disorder transition takes place reversibly at ambient pressure, ,, and (iii) the orientational glass-transition temperature is below the hydrogen order–disorder transition boundary, , which means that the water molecules have enough mobility to rearrange the configurations.…”
mentioning
confidence: 99%
“…To enhance molecular reorientation and suppress orientational glass formation, it is effective to dope disordered phases with a small amount of acid or base. It is known that KOH doping effectively promotes the ice I h -to-XI disorder-to-order transformation , and HCl doping does the ice V-to-XIII, ,, VI-to-XV, ,,, and XII-to-XIV , transitions.…”
mentioning
confidence: 99%